ANALISIS CUSTOMER EXPERIENCES DAN SERVICESCAPE TERHADAP REPURCHASE INTENTION DAN RELATIONSHIP MARKETING (STUDY KASUS PT. NAYRA MULTI JAYA) - Mubarok, Lusi Silviana; Pristiyono; Elvina (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Now, the factors that influence Repurchase Intention and Relationship Marketing are Customer Experience and Servicescape. The purpose of this study is to identify the impact of customer experience and servicescape in influencing repurchase intention will also affect the relationship marketing of PT. Nayra Multi Jaya by using the SmartPLS 4.0 analysis tool in proving the direct effect between the independent and dependent variables. Data is collected through probability sampling. Customers of PT Nayra Multi Jaya received questionnaires and direct interviews to obtain data for this study. The name and age of the respondent are included in the descriptive analysis method used to explain the identity of the respondent. The results found in the study show that partially customer experience and serviceescape affect repurchase interest and customer service affects relationship marketing.